PENGARUH KUALITAS PRODUK DAN CITRA PRODUK TERHADAP LOYALITAS PENGGUNA IPHONE MELALUI KEPUASAN PENGGUNA SEBAGAI VARIABEL INTERVENING STUDI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MURIA KUDUS - Defri Pratama, Muchammad Atha (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This research aims to analyze the influence of product quality and product image on user loyalty with user satisfaction as an intervening variable. This research data uses primary data in the form of a questionnaire. The sampling method used a purposive sampling method with a sample of 120 respondents. The data analysis used in this research is a structural equation model. The research results state that product quality and product image have a positive and significant effect on user satisfaction. Product image and user satisfaction have a positive and significant effect on user loyalty, while product quality does not have a positive and significant effect on user loyalty.